The El Niño–Southern Oscillation pattern effect - Ceppi,P; Fueglistaler,S (Geophysical Research Letters, 2021)
El Niño–Southern Oscillation (ENSO) variability is accompanied by out-of-phase anomalies in the top-of-atmosphere tropical radiation budget, with anomalous downward flux (i.e., net radiative heating) before El Niño and anomalous upward flux thereafter (and vice versa for La Niña). Here, we show that these radiative anomalies result mainly from a sea surface temperature (SST) “pattern effect,” mediated by changes in tropical-mean tropospheric stability. These stability changes are caused by SST anomalies migrating from climatologically cool to warm regions over the ENSO cycle. Our results are suggestive of a two-way coupling between SST variability and radiation, where ENSO-induced radiative changes may in turn feed back onto SST during ENSO.